2020
DOI: 10.1177/1178646920964825
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tryptophan and Tyrosine in Executive Function and Reward Processing

Abstract: The serotonergic precursor tryptophan and the dopaminergic precursor tyrosine have been shown to be important modulators of mood, behaviour and cognition. Specifically, research on the function of tryptophan has characterised this molecule as particularly relevant in the context of pathological disorders such as depression. Moreover, a large body of evidence has now been accumulated to suggest that tryptophan may also be involved in executive function and reward processing. Despite some clear differentiation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 161 publications
(172 reference statements)
0
20
0
Order By: Relevance
“…Notably, the neurochemical consequences of tryptophan depletion are complex and still not fully understood (Aquili, 2020). Although there is strong evidence that acute tryptophan depletion lowers 5‐HT levels in the brain, it has also been shown that their effect can vary depending on the dose administered (Yatham et al, 2001).…”
Section: Serotonin and Social Adaptationmentioning
confidence: 99%
“…Notably, the neurochemical consequences of tryptophan depletion are complex and still not fully understood (Aquili, 2020). Although there is strong evidence that acute tryptophan depletion lowers 5‐HT levels in the brain, it has also been shown that their effect can vary depending on the dose administered (Yatham et al, 2001).…”
Section: Serotonin and Social Adaptationmentioning
confidence: 99%
“…Tyrosine and tryptophan are essential precursors of neurotransmitters dopamine and serotonin, important for motivation and mood, respectively 23 , 24 . For instance, acute tyrosine and tryptophan depletions cause impairments in reward processing (e.g., reduced motivation for rewards) and lower mood 25 , 26 . Furthermore, studies have implicated a key role for dopamine in motivating information-seeking and exploration, as shown by the dopamine reward circuitry signaling the value of information 4 , 27 , 28 , and the relief of curiosity 29 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, acute tyrosine and tryptophan depletions cause impairments in reward processing (e.g. reduced motivation for rewards) and lower mood 24,25 . Furthermore, studies have implicated a key role for dopamine in motivating information-seeking and exploration, as shown by the dopamine reward circuitry signalling the value of information 4,26,27 , and the relief of curiosity 28 .…”
Section: Introductionmentioning
confidence: 99%